Effectiveness of interventions to prevent drowning among children under age 20 years: a global scoping review - Ashraf, Lamisa; Zia, Nukhba; Vincenten, Joanne; Mackay, J. Morag; Agrawal, Priyanka; Green, Abigail; Bachani, Abdulgafoor M. (Frontiers in Public Health, 2024)
Background: Drowning is a leading cause of death among young children. The United Nations Resolution on global drowning prevention (2021) and World Health Assembly Resolution in 2023 have drawn attention to the issue. This scoping review synthesizes the current evidence on the effectiveness of child drowning prevention interventions since the 2008 World Report on Child Injury Prevention and implications for their implementation. Methods: Quantitative studies published between 2008-2023 focusing on interventions targeting unintentional injuries, including drowning, among children and adolescents under age 20 years were searched on Cochrane Database of Systematic Reviews, Epistemonikos, PubMed, and Embase. Relevant data on interventions were extracted using a pre-defined template on Microsoft Excel. This scoping review focuses on the interventions addressing drowning. Results: Overall, 12 studies fulfilled the inclusion criteria. Evidence generated between 2008 and 2023 support the effectiveness of introducing barriers around water bodies, immediate resuscitation and first-responder training, and use of personal floatation devices (PFDs). Basic swimming and water safety skills training for children ages 6 years and older, and enacting and enforcing regulations on pool fencing and PFD use were found to be promising based on new evidence published since 2008. This scoping review also found evidence on new interventions studied since 2008, such as close adult supervision, inspections of safety standards of pools, and the use of door barriers and playpens, all of which demand further research to ensure context-specific implementation in LMICs. Conclusion: While there is evidence to support both existing and new interventions, most of the available interventions are still classified as promising and emerging, underlining the need for further evaluation of those interventions in diverse settings (including low and middle- income) through effectiveness studies and implementation research. In addition, it is important to highlight the nexus between drowning prevention and the Sustainable Development Goals to advocate multisectoral and interdisciplinary collaboration, to influence the broader child health agenda.